2008
DOI: 10.1387/ijdb.072284mb
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting of mammalian male gametes is gene specific and does not occur at a single stage of differentiation

Abstract: Epigenetic modifications such as DNA methylation and alterations to chromatin structure have been proposed as hallmarks of imprinting in somatic cells after fertilization. In the germ cell line, gene imprinting needs to be reset in order to transmit the correct sex-specific imprinting pattern to the next generation. The precise timing of imprint erasure and re-establishment for many genes remains to be determined and precise molecular mechanisms of genomic imprinting have not yet been fully characterized. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Sex-specific methylation patterns are then established during germ-cell differentiation (6,13). In the male mouse germline, remethylation is initiated after prenatal mitotic arrest in prospermatogonia and proceeds in a gene-specific manner until the end of the pachytene spermatocyte stage (14)(15)(16)(17)(18). In the female germline, methylation patterns also are established in a gene-specific manner; however, this occurs during later stages of oocyte development (19)(20)(21)(22).…”
Section: In Vitro Culture Interferes With Critical Windows For Epigenmentioning
confidence: 99%
“…Sex-specific methylation patterns are then established during germ-cell differentiation (6,13). In the male mouse germline, remethylation is initiated after prenatal mitotic arrest in prospermatogonia and proceeds in a gene-specific manner until the end of the pachytene spermatocyte stage (14)(15)(16)(17)(18). In the female germline, methylation patterns also are established in a gene-specific manner; however, this occurs during later stages of oocyte development (19)(20)(21)(22).…”
Section: In Vitro Culture Interferes With Critical Windows For Epigenmentioning
confidence: 99%
“…The sperm-specific methylation patterns are then established during germ cell differentiation (Hajkova et al ., 2002; Carrell, 2012). Remethylation is initiated after prenatal mitotic arrest in prospermatogonia and proceeds in a gene-specific manner until the end of the pachytene spermatocyte stage (Rousseaux et al ., 2005; Oakes et al ., 2007; Boyano et al ., 2008). Whole genome bisulfite sequencing revealed that the promoter regions of most developmentally important genes are hypomethylated in spermatozoa (Hammoud et al ., 2009), most likely to ensure their rapid activation in the early embryo.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is commonly accepted that the establishment of maternally methylated DMRs occurs after birth in females, simultaneously, in the oocytes at the growing oocyte stage (Lucifero et al, 2004; Morgan et al, 2005; Ferguson-Smith, 2011; Smith and Meissner, 2013). In males there is evidence that de novo methylation starts late in fetal life or during the newborn period, and at least for some loci and some species, it seems to be acquired during post-natal life (Davis et al, 1999; Kerjean et al, 2000; Lucifero et al, 2004; Morgan et al, 2005; Boyano et al, 2008; Smith and Meissner, 2013; Suzuki et al, 2013). Boyano et al (2008) have observed that genomic imprinting of H19 genes is established at different stages of germ cells differentiation during post-natal life in male mice.…”
Section: Hypothesis and Discussionmentioning
confidence: 99%
“…In males there is evidence that de novo methylation starts late in fetal life or during the newborn period, and at least for some loci and some species, it seems to be acquired during post-natal life (Davis et al, 1999; Kerjean et al, 2000; Lucifero et al, 2004; Morgan et al, 2005; Boyano et al, 2008; Smith and Meissner, 2013; Suzuki et al, 2013). Boyano et al (2008) have observed that genomic imprinting of H19 genes is established at different stages of germ cells differentiation during post-natal life in male mice. Likewise, Suzuki et al (2013) have reported that the H19 DMR undergoes de novo methylation only after 34 days post-partum in the germ line of the marsupial Tammar Wallaby .…”
Section: Hypothesis and Discussionmentioning
confidence: 99%